Portable split-level technology in café and Surabi as a design reference theme - Ghina Ghifari; Zahrah Aghnia Sholihah; Nurul Anisa Fitriani; Dedeng Hirawan; Herry Saputra (Universitas Komputer Indonesia, 2021)
Development in Indonesia is very rapid. The dense population in Indonesia makes buildings denser and lifestyles are increasingly modern so that traditional culture begins to erode by the times. Café is one of the most popular places in this day and age. The existence of a café that sells traditional food with modern concept buildings, makes visitors more interested in coming. The study aimed to design a space composition at Café Surabi by taking a concept based on the fibber shape of surabi. The pattern of space sharing in cafes and Kouta visitors who expand is an obstacle experienced by café owners in the comfort of café visitors. With the design of a high-tech ceiling that can be operated to scratch the remote. Use development methods or Research Development (RnD). This RnD method is carried out using 10 steps, namely potential and problems, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, product revisions, and mass production. The results of our research explain the planning and design of a café in the Surabi room. The composition of space is a characteristic of a space that affects the comfort of the interest of café visitors. It can be noted that the composition of the café surabi room gives a new season to the café by paying attention to the building structure